Late Triassic (Norian-Rhaetian) bivalves from the Antimonio Formation, northwestem Sonora, Mexico - Christopher A. McRoberts (Revista Mexicana de Ciencias Geológicas)
The Norian-Rhaetian bivalve fauna from the upper part of Antimonio Formation is taxonomically and ecologically more diverse than previously reported. Of the 10 bivalve taxa described herein, eight have never been previously described from Sonora and at least four represent previously unknown forms… in order to continue, download the full paper in PDF.